Fossil pollen records indicate that Patagonian desertification was not solely a consequence of Andean uplift - Palazzesi, Luis (2014)
The Patagonian steppe—a massive rain-shadow on the lee side of the southern Andes—is assumed to have evolved ~15–12 Myr as a consequence of the southern Andean uplift. However, fossil evidence supporting this assumption is limited. Here we quantitatively estimate climatic conditions and plant richness for the interval ~10–6 Myr based on the study and bioclimatic analysis of terrestrially derived spore–pollen assemblages preserved in well-constrained Patagonian marine deposits. Our analyses indicate a mesothermal climate, with mean temperatures of the coldest quarter between 11.4 °C and 16.9 °C (presently ~3.5 °C) and annual precipitation rarely below 661 mm (presently ~200 mm). Rarefied richness reveals a significantly more diverse flora during the late Miocene than today at the same latitude but comparable with that approximately 2,000 km further northeast at mid-latitudes on the Brazilian coast. We infer that the Patagonian desertification was not solely a consequence of the Andean uplift as previously insinuated.